Finite Volume Simulation of the Viscoelastic Fluids At An Expansion Flow (University of Thi-Qar Journal for Engineering Sciences, 2020)
Numerical simulation of viscoelastic fluid flow of the upper-convected Maxwell (UCM) type by finite volume on collected grid arrangement for the steady laminar flow through the 1:4 planer expansion has been obtain for a range of Deborah numbers. The conservation equations and the constitutive equations have been solved by using the finite volume numerical method on a collected grid arrangement with using the power low scheme for the momentum equations and the upwind scheme for the constitutive equations. The solution of the non-linear algebraic equation from the discretization process was obtained by using the Tri-Diagonal Matrix Algorithm (TDMA). The solution was verified with grid refinement. It is discovered that increasing the elasticity level lead to increasing the pressure, stresses and decreases the recirculation zones, where increasing Deborah number from 0 to 1.5 causes the pressure to increase by 2.6%. The finite volume method (FVM) shows that it capable for the numerical simulation of viscoelastic fluid flow with high speed to get the final solution and low computational cost